Absolute efficiency measurements with the 10B based Jalousie detector - Modzel, Gerd; Henske, M.; Houben, A.; Klein, Martin; Köhli, Markus; Lennert, Peter; Meven, M.; Schmidt, C. J.; Schmidt, Ulrich; Schweika, W. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
The 10B based Jalousie detector is a replacement for 3He counter tubes, which are nowadays less affordable for large area detectors due to the 3He crisis. In this paper we investigate and verify the performance of the new 10B based detector concept and its adoption for the POWTEX diffractometer, which is designed for the detection of thermal neutrons with predicted detection efficiencies of 75-50% for neutron energies of 10-100meV, respectively. The predicted detection efficiency has been verified by absolute measurements using neutrons with a wavelength of 1.17Å (59meV).